Analysis of saturation flow on isolated lanes of controlled intersections with significant traffic intensity - Murovanyi, Igor; Mazyliuk, Pavlo (Видавництво Львівської політехніки, 2020)
The methods and results of the investigation of intervals between vehicles during queue dissipation before controlled intersections with the further determination of saturation flow are reviewed in this paper. Having reviewed existing methods of determining the saturation in traffic flows, those are determined which provide the most certain results in conditions of intensive movement and take into account quite a large number of impact factors. Such methods are based on experimental measurement of intervals between vehicles during their passage through the stop-line in different directions of the controlled intersection. For the completeness of the analysis of such intervals, such factors are considered additionally as traffic composition and use of lanes by directions. Objects of the research are controlled intersections on approaches to which the slope is absent, there is no pedestrian and cyclist movement during the performance of turn, and conflicting traffic flows and also public transport stops in the zone of the intersection. The transitional research result is the determination of the number of vehicles that pass the stop-line during the permissive signal and time intervals between them, and the final result is the oncoming of saturation period on the lanes of straight and turns movement depending on traffic flow composition.
Keywords: controlled intersection; the time interval between vehicles; saturation flow; traffic flow; traffic delay; traffic intensity; traffic flow composition; roadway; traffic light cycle; traffic light control; road users